The effects of a four-month skateboarding intervention on motor, cognitive, and symptom levels in children with ADHD - Christ, Tabea; Boström, Kim Joris; Ohrmann, Patricia; Britz, Henrike; Wagner, Heiko; Bohn, Christiane (Frontiers in Pediatrics, 2024)
Objectives and methods: This study aimed to investigate whether a four-month skateboarding workshop can positively affect attention-focusing skills and postural control in terms of static and dynamic balance in addition to symptoms of ADHD in school-aged children (N = 58). Kinematic and kinetic movement analysis, attention-focusing tests as well as symptom questionnaires were employed to measure differences caused by the skateboarding intervention. A weekly skateboarding workshop was conducted with children diagnosed with ADHD which intended to encourage children to autonomously engage in physical activity. Group differences were analyzed using a generalized linear mixed model. A partial correlation was used to investigate possible relationships between the variables.Results: A preceding analysis confirmed that children with ADHD perform statistically significantly inferior in the employed tests of balance and concentration ability than unaffected peers of the same age. The main analysis showed that after the skateboarding intervention, children with ADHD were able to improve cognitive and motor test performances as well as symptom expression significantly.Significant improvements were likewise found in the waitlist control group, these were however less pronounced compared to those of the skateboarding intervention group. The correlation analysis revealed that there is no reciprocal influence between cognitive and motor skills, nor between motor skills and ADHD symptomatology in the present patient group. Possible explanations are discussed.Skateboarding as a form of movement intervention can be considered an effective method for children with ADHD to deal with their symptoms and deficits. An intervention period of four months has helped children with ADHD discover and embrace an informal sport like skateboarding, thereby finding enjoyment in movement and practice a skill from intrinsic motivation. To retain the benefits, it is advisable to practice a sport on a long-term basis. Thorough conceptualizations to implement this type of therapy await further research.